2000
DOI: 10.1038/sj.mp.4000726
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor D2 Ser/Cys 311 variant is associated with delusion and disorganization symptomatology in major psychoses

Abstract: The D2 receptor (DRD2) is a binding site of many psychoactive drugs and it has been proposed as a genetic risk factor for psychiatric disorders. The aim of this investigation was to study the DRD2 S311C variant in major psychoses. We studied 1182 inpatients with diagnoses of bipolar disorder (n = 480), major depressive disorder (n = 269), schizophrenia (n = 366), delusional disorder (n = 44), psychotic disorder not otherwise specified (n = 23) and 267 healthy controls. Eight hundred and eighty-seven subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
3

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 59 publications
2
33
3
Order By: Relevance
“…The magnitude of this effect was quite sizable (odds ratio [OR] ¼ 3.1; 95% confidence interval [CI] ¼ 1.4-6.7; P ¼ 0.004), and the polymorphism also was shown to alter the physiology and function of the receptor [Itokawa et al, 1993]; thus, this promising association quickly became the object of widespread replication efforts, most of which failed. In fact, only two of the 23 subsequent association studies of schizophrenia and the DRD2 Ser311Cys polymorphism found a significant relationship [Serretti et al, 2000;Jonsson et al, 2003]. As a consequence, the initial finding of association became widely regarded as a type-I inferential error [Verga et al, 1997]; however, it remained unclear if these failed replication attempts were due to the low power of individual studies, etiologic heterogeneity across samples, or random error in the absence of a true effect.…”
Section: Introductionmentioning
confidence: 96%
“…The magnitude of this effect was quite sizable (odds ratio [OR] ¼ 3.1; 95% confidence interval [CI] ¼ 1.4-6.7; P ¼ 0.004), and the polymorphism also was shown to alter the physiology and function of the receptor [Itokawa et al, 1993]; thus, this promising association quickly became the object of widespread replication efforts, most of which failed. In fact, only two of the 23 subsequent association studies of schizophrenia and the DRD2 Ser311Cys polymorphism found a significant relationship [Serretti et al, 2000;Jonsson et al, 2003]. As a consequence, the initial finding of association became widely regarded as a type-I inferential error [Verga et al, 1997]; however, it remained unclear if these failed replication attempts were due to the low power of individual studies, etiologic heterogeneity across samples, or random error in the absence of a true effect.…”
Section: Introductionmentioning
confidence: 96%
“…These have reported associations between polymorphisms in DRD4 and catatonia 18 and delusions, 19 DRD2 and disorganization and delusions 20 CCK and positive symptoms, 21 5-HT promoter and auditory hallucinations 22 and affective symptoms, 23 HkCa3 and negative symptoms 24 and BDNF and DAT1 and negative symptoms. 23 Moreover, these polymorphisms were not associated with illness in these samples.…”
Section: Susceptibility Vs Modifier Genesmentioning
confidence: 99%
“…In the dopamine D2 receptor (DRD2) gene, there is a polymorphism that results in an amino acid change in the receptor protein (from serine to cysteine at position 311; hence referred to as Ser311Cys). Several studies have not found a significant association between this polymorphism and delusional disorder (Morimoto et al, 2002;Sasaki et al, 1996;Serretti, Lattuada, Lorenzi, Lilli, & Smeraldi, 2000). A polymorphism in the dopamine D3 receptor (DRD3) gene, which results in a serine to glycine substitution (Ser9Gly), has shown association with delusional disorder in one study (Di Bella et al, 1994), but not in another (Morimoto et al, 2002).…”
Section: Molecular Genetic Studiesmentioning
confidence: 97%